Hepatitis G virus infection in fulminant hepatic failure. Issue 5 (1st November 1997) - Sáiz, J C; Sans, M; Mas, A; Olmedo, E; Forns, X; López-Labrador, F X; Restrepo, J C; Costa, J; Salmerón, J M; Guilera, M; Ampurdanés, S; Sánchez-Tapias, J M; et al.
Abstract : Background —RNA sequences of the recently identified hepatitis GB virus C (HGBV-C), also named hepatitis G virus (HGV), have been detected in patients with idiopathic fulminant hepatic failure (FHF) but the role of this agent in the disease remains controversial. Aims —To investigate the presence and implications of HGV infection in a large series of Spanish patients with FHF. Patients —Sixty eight patients with FHF, including 19 with idiopathic disease, were studied. In 28 cases, studies were performed before and after liver transplantation. For comparison 200 volunteer blood donors and 22 patients transplanted for chronic liver disease were also studied. Methods —HGV RNA was measured in serum by reverse transcriptase polymerase chain reaction of the 5′ non-coding region. Results —Evidence of HGV infection was found in 3% (6/200) of blood donors and in 19% (13/68) of patients with FHF. HGV infection was more frequent in patients with hepatitis B (24%, 6/25) or hepatitis D (42%, 5/12), than in patients with idiopathic disease (11%, 2/19). Half of the patients with HGV infection used illicit intravenous drugs. Specific clinical features associated with HGV infection were not identified. A very high rate of infection with HGV was observed in patients who underwent liver transplantation, either for FHF (60%, 15/24) or chronic liver disease (45%, 9/20). Conclusions —In our geographical area, HGV infection is relatively frequent in FHF, but it does not seem to play a major role in idiopathic cases.